The impact of timely cancer diagnosis on age disparities in colon cancer survival. Issue 7 (September 2021) - Pilleron, Sophie; Maringe, Camille; Charvat, Hadrien; Atkinson, June; Morris, Eva J A; Sarfati, Diana
Abstract: Objective: We described the role of patient-related and clinical factors on age disparities in colon cancer survival among patients aged 50–99 using New Zealand population-based cancer registry data linked to hospitalisation data. Method: We included 21, 270 new colon cancer cases diagnosed between 1 January 2006 and 31 July 2017, followed up to end 2019. We modelled the effect of age at diagnosis, sex, ethnicity, deprivation, comorbidity, and emergency presentation on colon cancer survival by stage at diagnosis using flexible excess hazard regression models. Results: The excess mortality in older patients was minimal for localised cancers, maximal during the first six months for regional cancers, the first eighteen months for distant cancers, and over the three years for missing stages. The age pattern of the excess mortality hazard varied according to sex for distant cancers, emergency presentation for regional and distant cancers, and comorbidity for cancer with missing stages. Ethnicity and deprivation did not influence age disparities in colon cancer survival. Conclusion: Factors reflecting timeliness of cancer diagnosis most affected age-related disparities in colon cancer survival, probably by impacting treatment strategy. Because of the high risk of poor outcomes related to treatment in older patients, efforts made to improve earlier diagnosis in older patients are likely to help reduce age disparities in colon cancer survival in New Zealand.